2020
DOI: 10.1002/celc.202000072
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ru‐Doped VN by a Soft‐Urea Pathway as an Efficient Catalyst for Hydrogen Evolution

Abstract: Unraveling the effect of metal doping on the intrinsic activity of metal nitride remains a grand challenge. Herein, Ru (Rh)‐doped vanadium nitride are successfully synthesized via a simple soft‐urea pathway. In comparison, the Ru‐doped VN electrocatalyst exhibits much better HER performance than Rh‐doped VN electrocatalysts. The optimal Ru‐VN catalyst delivers a low overpotential of 134 (144) mV at current density of 10 mA cm−2, and a low Tafel slope of 35 (73) mV dec−1 in acidic (alkaline) condition. Such exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…Many investigated nitride catalysts contained impurity phases and/or were composite materials, with for example, high surface area metalfoam or carbons. [14][15][16][17][18] This makes the explanation of their catalytic properties by theory a complex task because it is very challenging to build reliable computational models for multiphase systems. 12,[19][20][21][22] On the other hand, the electrochemical tests on materials that are free from substrates and secondary phases can provide a robust benchmark for comparison between existing and development of future nitride materials.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigated nitride catalysts contained impurity phases and/or were composite materials, with for example, high surface area metalfoam or carbons. [14][15][16][17][18] This makes the explanation of their catalytic properties by theory a complex task because it is very challenging to build reliable computational models for multiphase systems. 12,[19][20][21][22] On the other hand, the electrochemical tests on materials that are free from substrates and secondary phases can provide a robust benchmark for comparison between existing and development of future nitride materials.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium nitride-based materials and their hybrids with metals [ 199 , 225–227 ], and metal sulfides [ 228 ] have been used as electrocatalysts for HER applications. For example, Zhang et al demonstrated the preparation of Co, N-codoped porous vanadium nitride with a high BET surface area (21.4 m 2 /g) and presented its excellent HER activity.…”
Section: Electrochemical Production Of Hydrogenmentioning
confidence: 99%
“…The prepared materials showed a small overpotential of 179 mV at 10 mA cm −2 and a Tafel slope of 123 mV/dec [ 226 ]. Notably, the pyrrolic and graphitic N sites and Co doping bring additional active sites and improve conductivity while the material is highly stable for up to 100 h. In another work by Wang et al, Ru doped VN was used as an effective HER catalyst where the optimized material Ru-VN-2 showed excellent Tafel slop of 35 mV/dec and a small overpotential of 134 mV at 10 mAcm −2 in 0.5 M H 2 SO 4 solution [ 225 ]. Further, for the optimized Ru doping, a large turnover frequency of 1.77 s −1 at 200 mV and stability for 20 h without much degradation is achieved, showing the importance and effect of Ru doping.…”
Section: Electrochemical Production Of Hydrogenmentioning
confidence: 99%
“…In particular, the atom doping in TMNs was reported to be effective in regulating surface active sites, structure, metallicity and hydrogen adsorption free energy (Δ G H* ). 18 For example, Luo et al doped Cr atoms into the Co 4 N, which could optimize the hydrogen binding abilities of Co active sites, and thus achieving a high HER activity. 25 It can be concluded that doping in TMNs would contribute to improving the utilization efficiency of metal ions and develop efficient cocatalysts, which is still lacking in-depth exploration to date.…”
Section: Introductionmentioning
confidence: 99%